A graphical approach to basic signal processing theories - Peng, Jun Wen. (2010)
Digital Signal Processing (DSP) deals with the representation of signals in the digital form, and with the processing of these signals and the information they possess. With the increase in extensive research being done in the field of signal processing, along with a corresponding increase in the sophisticated development in DSP processors, digital signal processing has become an integral part of many commercial applications. Some of the important processing techniques and theories that were developed decades ago lay the foundation of many aspects in advance signal processing methods. This project is concerned with the fundamental concepts of signal processing theories and this is addressed through the development of various programs that will illustrate basic signal theories such as fourier transform, sampling, filtering etc using a graphical approach to allow students to gain a solid foundation in signal processing knowledge before proceeding to more in-depth analysis of further theoretical models. The main software that the project will be utilizing is Matlab as the robustness of Matlab is extensive enough to allow the user to expand their knowledge of signal and systems through the interactions with the various programs designed.